Natural Compounds Targeting Oncogenic Signaling Networks in Glioblastoma: Molecular Mechanisms, Translational Advances, and Clinical Perspectives - Mehrukh Zehravi; Md Abul Hassan; Md. Al Amin; Sherouk Hussein Sweilam; Jeetendra Kumar Gupta; Ramenani Hari Babu; Pericharla Venkata Narasimha Raju; Krishna Vamsi Kandimalla; Phanindra Erukulla; Patibandla Jahnavi; Rajeshwar Vodeti; Abdul Ajeed Mohathasim Billah; et al. (Brain and Behavior, 2026)
ABSTRACT Purpose Glioblastoma (GBM), the most aggressive and common primary brain tumor in adults, has a poor prognosis, rapid growth, and resistance to treatment. Abnormal activation of signaling pathways like PI3K/AKT/mTOR, MAPK/ERK, JAK/STAT, Wnt/β‐catenin, NF‐κB, and Notch facilitates uncontrolled proliferation, angiogenesis, invasion, and immune evasion. Conventional treatments are insufficient in modifying complex networks, necessitating the urgent need for novel multitargeted treatments. Natural compounds are increasingly being considered as potential treatments for GBM due to their ability to control multiple oncogenic pathways simultaneously and their lower toxicity compared to synthetic medicines. This review provides an integrated and translational perspective on GBM, differing from past reviews that focused on the anticancer effects of individual phytochemicals or specific signaling pathways. We discussed the relationship between natural compounds and key oncogenic signaling networks, focusing on GBM pathogenesis, blood–brain barrier penetration, nanotechnology‐assisted delivery, and strategies combining standard therapies. Furthermore, this review critically distinguished in vitro, in vivo, and clinical evidence, focusing on bioavailability challenges, ongoing clinical trials, and future opportunities in precision oncology. Method To ensure the inclusion of the most appropriate articles in this review, an in‐depth search was carried out on prominent medical, biological, and chemical databases, including Scopus, PubMed, and Web of Science. The search strategy employed combinations of Medical Subject Headings and Boolean operators, focusing on terms related to glioblastoma, natural compounds, and various molecular mechanisms involved in drug delivery, clinical trials, and diagnosis. Finding These natural compounds demonstrated potential in preclinical GBM models for inducing apoptosis, suppressing angiogenesis, modulating oxidative stress, and enhancing chemosensitivity. Additionally, some natural compounds can cross the blood–brain barrier, thereby increasing their translational significance. The use of molecular diagnostics, including biomarkers, genetic profiling, and advanced imaging, has significantly improved early identification and patient stratification. Specific compounds with strong translational potential, such as curcumin, resveratrol, EGCG, quercetin, berberine, and luteolin, are highlighted along with their main molecular targets and therapeutic effects. The integration of natural compounds into precision‐based therapy approaches has been made possible. Conclusion Future research aims to combine molecular diagnostics with phytochemical therapies, validate clinical trial outcomes, and enhance bioavailability with nanotechnology delivery systems. The combination of natural compounds shows potential for creating safe, effective, and pathway‐specific treatments for GBM.